2016
DOI: 10.21577/0100-4042.20160192
|View full text |Cite
|
Sign up to set email alerts
|

Células solares sensibilizadas por pontos quânticos

Abstract: publicado na web em 25/11/2016 QUANTUM DOT-SENSITIZED SOLAR CELLS. Quantum dot solar cells (QDSC) have been subject of extensive research in recent years. QDSC, as a promising alternative to existing solar cells, are among the candidates for next-generation photovoltaic devices that require low cost, high efficiency, so that quantum dots stand out for their unique features and versatile desirable on photovoltaic systems. The rapid development of QDSC provided a significant increase in energy conversion efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
1
2
0
1
Order By: Relevance
“…In general, the experimental cells presented low values of FF, ranging from 0.2 to 0.5, considered quite resistive systems. The effects can be noted in the efficiency values, in which the resistivity interferes directly [19]. The DSSCs manufactured in this work displayed electrical performance as reported in the literature [2,9,22].…”
Section: Electrical Characterization Of Dsscssupporting
confidence: 54%
See 2 more Smart Citations
“…In general, the experimental cells presented low values of FF, ranging from 0.2 to 0.5, considered quite resistive systems. The effects can be noted in the efficiency values, in which the resistivity interferes directly [19]. The DSSCs manufactured in this work displayed electrical performance as reported in the literature [2,9,22].…”
Section: Electrical Characterization Of Dsscssupporting
confidence: 54%
“…This parameter can be obtained from the ratio between these powers (equation 1) and is directly related to the efficiency of the cell. The value of FF varies from 0 to 1, and the closer to 1 the less resistive the system is [19].…”
Section: Electrical Characterization Of the Dssc'smentioning
confidence: 99%
See 1 more Smart Citation
“…121,122 As células solares baseadas em QDs de ZnO já atingiram um PCE de 15,49%. 123 Vitoreti e colaboradores 124 publicaram, recentemente, um artigo de revisão sobre células solares sensibilizadas por QDs, retratando muito bem o estado da arte para esta aplicação.…”
Section: Células Solaresunclassified
“…[11] This class of solar cells includes quantum dotsensitized solar cells (QDSSCs), organic solar cells and, more recently, perovskites solar cells. [6][7][8]12,13] DSSCs can be considered a milestone in the development of emerging technology solar cells, as Gratzel demonstrated that a photoanode sensitized by molecular dye could achieve a solar ECE value between 7.1% and 7.9%. [11,14] Such cell had low-costs production and great potential to replace silicon-based photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%